Prevalence of ampicillin-resistant strains of Haemophilus influenzae causing systemic infection. - Lerman, S J (1980)
Surveillance of Haemophilus influenzae bacteremia and meningitis in Omaha during the 6-year period 1974 to 1979 revealed no upward trend in ampicillin resistance. The overall proportion was 5%, and the annual prevalence ranged from 0 to 9%.